Analysis of Readiness Factors in Implementing the Clinical Research Unit Concept at Yarsi Hospital - Listiyani Listiyani; Sri Wuryanti; Dicky Budiman; Chandra Yusuf; Danial Rasyid; Soroy Lardo (International Journal of Advanced Health Science and Technology, 2025)
This study explores the readiness factors required to implement a Clinical Research Unit (CRU) at YARSI Hospital. The research was driven by the necessity to enhance clinical research in Islamic hospitals that currently lack an integrated CRU. Utilizing a qualitative exploratory approach with a case study design, the study involved interviews, observations, and document analysis. The findings identified five key dimensions influencing CRU readiness: human resources, regulations, funding, infrastructure, and the organizational culture rooted in Islamic values. This study integrates organizational capability theory, institutional theory, and maqashid shariah principles, recommending the establishment of Indonesia's first Sharia-compliant CRU